La Petite À La Burqa Rouge by Tahar Ben Jelloun: Orientalization of the Tale Le Petit Chaperon Rouge by Charles Perrault - Tania Intan; Amaliatun Saleha (Eralingua: Jurnal Pendidikan Bahasa Asing dan Sastra, 2020)
Tales generally comes from oral traditions, which were later written to be passed for generations. One of the prominent European tale authors in the 17th century was Charles Perrault whose works have been adapted by literary authors throughout the world. Tahar Ben Jelloun, a francophone author from Morocco, performed reécriture on Perrault’s stories in his book Mes Contes de Perrault (2014). This study identifies the new elements Ben Jelloun gives to the tale Le Petit Chaperon Rouge with the result in the form of a short story called La Petite à la Burqa Rouge. The two texts which spanned four centuries were examined using descriptive analysis method. Results of the study showed that despite the maintenance of the main sequence of Charles Perrault’s tale, Ben Jelloun carries out the orientalization process on the tale Little Red Riding Hood in the forms of text delocalization, time and place transpositions, physical and mental reconstructions of the characters and the infiltration of feminist ideology and social criticism. Ben Jelloun’s active reception should be given appreciation as to the addition of colors and new ideas without any alteration on the old works